2020
DOI: 10.7554/elife.60581
|View full text |Cite
|
Sign up to set email alerts
|

Full-length Plasmodium falciparum myosin A and essential light chain PfELC structures provide new anti-malarial targets

Abstract: Parasites from the genus Plasmodium are the causative agents of malaria. The mobility, infectivity, and ultimately pathogenesis of Plasmodium falciparum rely on a macromolecular complex, called the glideosome. At the core of the glideosome is an essential and divergent Myosin A motor (PfMyoA), a first order drug target against malaria. Here, we present the full-length structure of PfMyoA in two states of its motor cycle. We report novel interactions that are essential for motor priming and the mode of recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 60 publications
7
54
0
2
Order By: Relevance
“…Stabilising residues include those between phospho-S19 in the N-terminal extension (NTE, brown) and K764 in the converter (green). PPS structure from [ 21 ]; Rigor-like structure (PDB: 6I7D, neck region and light chain outlines added as schematic, by extension of the last helix of the converter). C Genotyping PCR of PfMyoA-comp and PfMyoA-K764E lines confirmed that the WT p230p locus (green half arrow) is completely lost in PfMyoA-comp, while the integrated locus (IN, grey half arrow) is present.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stabilising residues include those between phospho-S19 in the N-terminal extension (NTE, brown) and K764 in the converter (green). PPS structure from [ 21 ]; Rigor-like structure (PDB: 6I7D, neck region and light chain outlines added as schematic, by extension of the last helix of the converter). C Genotyping PCR of PfMyoA-comp and PfMyoA-K764E lines confirmed that the WT p230p locus (green half arrow) is completely lost in PfMyoA-comp, while the integrated locus (IN, grey half arrow) is present.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, PfMyoA relies on a regulatory light chain or myosin tail interacting protein, MTIP, that binds the extreme end of the neck domain and unusually possesses a long, disordered N-terminal domain to anchor PfMyoA to the IMC [ 19 ]. Maximal in vitro activity of PfMyoA requires the binding of MTIP and a second essential light chain, PfELC [ 20 ], recently shown to stabilise the PfMyoA neck domain and to be critical for parasite replication [ 21 ]. The complex of PfMyoA and its light chains (the PfMyoA triple complex) is anchored to the IMC by a glideosome associated protein, PfGAP45 [ 22 , 23 ] and other GAP proteins embedded in the IMC membranes that together complete the MMC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GAP45, GAP50, GAP70, and GAPMs (Gaskins et al, 2004;Bullen et al, 2009;Freńal et al, 2010;Yeoman et al, 2011) together with Myosin A (MyoA) (Pinder et al, 1998;Baum et al, 2006;Ridzuan et al, 2012), the myosin A tail-interacting protein [MTIP in Plasmodium spp., or myosin light chain (MLC1) in T. gondii] (Herm- Götz et al, 2002;Bergman et al, 2003) and the "essential light chain 1" protein (ELC1) (Green et al, 2017) have been identified, a comprehensive and systemic identification of all components of the glideosome has not been performed. Recent years have uncovered some structural insights into this protein complex, but this improved understanding is still limited to individual components (Bosch et al, 2006;Bosch et al, 2007;Bosch et al, 2012;Boucher and Bosch, 2014) or to sub-complexes such as the trimeric structure composed of MyoA, ELC1 and MLC1 (Moussaoui et al, 2020;Pazicky et al, 2020) with no structural information on the entire glideosome complex. Another interesting group of proteins are the so called alveolins, an Alveolata specific and conserved multi-protein family encompassing at least 13 proteins ( Table 1) (Gould et al, 2008;Kono et al, 2012;Volkmann et al, 2012;El-Haddad et al, 2013;Tremp et al, 2014;Al-Khattaf et al, 2015).…”
Section: Defining the Inner Membrane Complex: Protein Composition Andmentioning
confidence: 99%